(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The conservatorship is a legal action to protect troubled banks from credit risk and bankruptcy risk that banks cannot hedge them .The Central Bank role has to protect the financial system from these risks by controlling and supervising. This research studied these risks and explained the role of The Central Bank. This research presented and analyzed the legal framework for supervision and the imposition of conservatorship bank to address the effects that have been achieved as a result of poor management and weak internal controls. Baraka Bank for Investment and Finance was a research sample to measure the financial ratios for the troubled bank, and analysis the results that led to put the conservatorship. The research depends on the hypothesis that shows (a correlation between the exercise of the Central Bank of the functions of the supervisory through conservatorship and protection of the financial system and return of troubled banks to exercise their work properly). A set of conclusions has been extracted from this study, these are(the tripping and failure or fiscal deficit are sides of a coin, that is a faltering starts with insolvency the Bank’s financial and will be invisible to depositors and customers as result of weak senior management and internal control, the conservator has the powers to take all appropriate action to ensure the functioning of the company or career, and the Financial Services Tribunal is absent in the decision conservatorship of the bank),Based on these conclusions the researcher put the following recommendations: the central bank control focus on the departments of banks through the application of corporate governance rules and procedures, and the possibility of increasing the period to object about the decision to appoint a conservator, be from the date of the decision to impose conservatorship, and the possibility of creating a joint venture to guarantee deposits and protect the funds of depositors and other creditors